Pengelolaan Emosi atas Validasi Sosial melalui Komunikasi Intrapersonal dalam Perspektif Stoikisme - Aminah Ummul Kamal; Diryo Suparto; Ike Desi Florina (Universitas Medan Area, 2026)
This study examines emotional management toward social validation through intrapersonal communication from a Stoic perspective among Generation Z in Tegal City. The study is motivated by individuals’ tendency to evaluate themselves based on recognition, appreciation, and social responses from their environment. This research employed a descriptive qualitative approach using purposive sampling involving 14 informants, consisting of main informants, key informants, and supporting informants. Data were collected through in-depth interviews, non-participant observation, and documentation, then analyzed using the interactive model of Miles and Huberman. The findings show that the lack of social validation in family relationships, friendships, work environments, and romantic relationships generates negative emotions such as disappointment, sadness, anger, feeling unappreciated, and feeling inadequate. These emotions are processed through intrapersonal communication, including sensation, perception, memory, and thinking. Stoic principles, such as the dichotomy of control, premeditatio malorum, amor fati, and inner discipline, help individuals reorganize their inner dialogue more rationally. This study concludes that intrapersonal communication and Stoicism can help Generation Z reduce dependence on external validation and build a more stable sense of self-worth.